Protective effects of inulin against lipopolysaccharide-induced oxidative stress in broiler chickens - Shang, Qinghui; Li, Hao; Han, Yan (Frontiers in Veterinary Science, 2025)
IntroductionThis study was conducted to evaluate the protective effects of inulin against lipopolysaccharide (LPS)-induced oxidative stress in broilers.MethodsA total of 108 1-day-old male Arbor Acres broilers were randomly allocated to 3 treatment groups with 6 replicates per group and 6 birds per replicate. The 3 groups were: (1) non-challenged broilers fed a corn-soybean meal basal diet (control group, CON); (2) LPS-challenged broilers fed the basal diet (LPS); (3) LPS-challenged broilers fed the basal diet supplemented with 15 g/kg inulin (LPS + Inulin).ResultsThe results showed that LPS administration inhibited activities of antioxidant enzymes and stimulated production of lipid peroxidation in multiple tissues including serum, liver, intestine, and muscle. Dietary inulin supplementation partially alleviated the negative effects of LPS on antioxidant capacity of these tissues, with the underlying mechanism involving the regulation of the Nrf2 signaling pathway.DiscussionCollectively, these findings indicate that inulin supplementation effectively alleviates LPS-induced oxidative stress, highlighting its potential as a feed additive in broiler diets to combat oxidative stress.